English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

can anyone help me with this - I was told to integrate

y= e^2x / √1-e^2x


anybody, please

thats ("y" is equal to "e" to the power of 2x) over (the squareroot of 1 - "e" to the power of 2x)

2006-11-11 09:45:18 · 2 answers · asked by robert d 2 in Science & Mathematics Mathematics

2 answers

Okay, assuming you mean:
∫e^(2x)/√(1-e^(2x)) dx
Let u=1-e^(2x), du=-2e^(2x) dx, dx = -1/2 e^(-2x)
-1/2 ∫1/√u du
-1/2 ∫u^(-1/2) du
-u^(1/2) + C
-√(1-e^(2x)) +C

2006-11-11 09:54:27 · answer #1 · answered by Pascal 7 · 1 0

y= e^2x / √1-e^2x
=(e^2x)/[(1-e^x)^(1/2))]
=(e^2x)/[(1)^(1/2)-(e^x)^(1/2)]
=[(e^2x)/[(1)^(1/2)]-[(e^2x)/[(e^x)^(1/2)]

2006-11-11 17:58:21 · answer #2 · answered by ? 3 · 0 1

fedest.com, questions and answers